Speed control of the V2 skating technique in elite cross-country skiers - Ohtonen, O.; Linnamo, V.; Lindinger, S. J. (International Journal of Sports Science & Coaching, 2016)
The aim was to examine how skiers control skiing speed using V2-skating. Subjects skied with three submaximal and maximal speeds on 100m 4° uphill. Cycle variables and force parameters form the arms and legs were analysed. Cycle rate increased up to the maximum speed. Cycle length increased from the slowest speed to the all other speeds. Pole force and delta leg force increased up to the maximum speed. Ranges of motions and angular velocities of kick flexion and extension with knee and hip joints increased till highest submaximal speed. Speed was regulated with cycle length and rate while the latter was dominant after ~5.0m/s. Higher speed was reached with higher forces from arms and legs while legs were emphasized with faster speeds. Higher forces were partly generated with greater vertical movement of the body, which might have elicited stretch-shortening cycle type of movement leading to greater force output.